하천수질정화용 토양여과의 여과용량 증대와 수질 개선을 위한 친환경 여재 특성 비교 - 기동원; 조강우; 원세연; 송경근; 안규홍 (대한상하수도학회, 2010)
Nowadays, the challenges of ensuring good water quality and quantity of river are becoming more important for human society, but there has been troublesome for purifying river water. In this study, we performed the fundamental study of a river water treatment system using riverside soil and eco-friendly optimal media for improving river water quality and can also treat a large amount of river water. As the results of the physical and chemical characterization of the two different soils (Kyungan and Chungrang, The Republic of Korea), which were collected from real stream sides in the Han River basin, and five kinds of media (zeolite, perlite, steel slag, woodchip and mulch), both soils were all classified as a sand, and effective size (D10) and uniformity coefficient (U) of the soil were about 0.2 mm and 4 or so, respectively. Through the batch and column experiments with the soil and eco-friendly media, zeolite and mulch were found to be efficient for decreasing nitrogen. In addition, steel slag was especially superior to the other media for phosphorus removal. From soil reforming tests volume ratios were 2.8, 1, and 1 of Kyungan soil, zeolite, and steel slag hydraulic conductivity of mixed soil was increased 1.30 x 10？² from 2.85 x 10？³ of Kyungan soil, and the removal efficiencies of nitrogen and phosphorus were also improved. These results show that reforming of the soil enhanced the purification of a large amount of water, and zeolite, mulch, and steel slag might be facilitated as proper functional media.